A luxury brand conceptualization proposal - Grande, Diogo Micael Pires Campo (2021)
This dissertation aims to broaden the understanding of luxury consumption and luxury brands. As there is no globally accepted definition of “luxury brand”, it is the purpose of this dissertation to propose a workable definition of luxury brand that can be employed to accurately describe the construct in the different product categories and sectors. Based on the literature review, a conceptual model was developed to explain the luxury brand construct through 12 dimensions: (1) awareness, (2) identity, (3) image associations, (4) aesthetics, (5) quality, (6) consumer expectations, (7) co-creation value, (8) autarchic financial value, (9) exclusivity, (10) authenticity, (11) desirability, and (12) emotional connections. To meet this goal, this dissertation overviews (a) the history of luxury, (b) the etymological origins and semantic evolution of its associated terms, (c) the analysis and critique of current definitions for luxury, luxury brands, and luxury products, (d) the meta-theoretical recommendations for the development of a good definition, (e) the consumer’s perceptions on luxury, and (f) the luxury brand’s managerial idiosyncrasies. Suggestions for future research are provided at the end of this dissertation.